Perception of Seed technology Training among Farm Women - Shobhana Gupta , K. L. Dangi; Shilpi Verma (Indian Journal of Extension Education, 2015)
In the present stud, farmwomen’s perception about the importance, need and adequacy of seed technology training conducted in two different KVKs of Rajasthan state was evaluated. Atotal of 120 farmwomen were randomly selected for the study. Data were collected through interview schedule. Results reveal that training on use of seed culture was found to be most important and training in new improved seed production technology was needed utmost in future to increase the production. Training on depth of sowing was found to be most adequate amomg majority of the respondents. Thus, farm women needed better training in some areas of seed technology and seed treatment. Therefore, there is a need to organize training programmes to stimulate higher participation of farmwomen in seed production so that women become more economically independent and improve financial status of the family